Can school health education improve students’ physical exercise time? Empirical research based on CEPS (2014–2015) survey data - Zhong, Huamei; Zhou, Jingjing; Xu, Dan; Liu, Tianbiao (Frontiers in Psychology, 2022)
School health education is an effective strategy for cultivating adolescent physical exer-cise habits by transmitting healthy knowledge; it helps to form healthy behaviours and encourages students to participate in physical exercise. To explore the relationship between school health ed-ucation and student participation in physical exercise, CEPS (China Education Penal Survey, 2014-2015) survey data were used to empirically analyse the impact of school health education on the time that students spend on physical exercise and the underlying mechanism of influence. The results showed that receiving a school health education lengthened the time that students spent on physical exercise. The same conclusion was obtained using robustness tests, including the instrumental variable method, propensity score matching, quantile regression and merge regression. The estimation results showed that compared with receiving health education in only primary school or secondary school, receiving health education in both primary and secondary school had a greater impact on students spending time on physical exercise. The test results of the mediation effect showed that receiving a school health education improved the time that students spend on physical exercise by improving students’ health perception and their sports interests. The heterogeneity test results showed that receiving a school health education had a more obvious impact on the physical exercise time of male students, nonrural resident students, and students from mul-ti-child households.